CLINICAL AND ELECTROCARDIOGRAPHIC SYNDROMES ASSOCIATED WITH THE RISKOF SUDDENCARDIAC DEATH: PATHOGENESIS, CLINICAL MANIFESTATIONS, DIAGNOSTIC CRITERIA, INDICATIONS FORGENETIC RESEARCHAND TREATMENT - V. V. Rezvan; I. M. Kuzmina; M. A. Vashkevich (Неотложная медицинская помощь)
PURPOSE. The problem of sudden cardiac death (SCD) is the most relevant in the modern cardiology , and if organic heart diseases exist, treatment strategy and prevention of SCD is developed , this problem is not solved in the patients without organic changes. Currently, a group of diseases, clinical and electrocardiographic syndromes, has emerged, that are closely associated with the formation of fatal arrhythmias. Special hazard of the course of these pathological conditions is due to the high risk of SCD, especially in young people. These diseases are not accompanied by structural changes in the myocardium and manifest themselves mainly by electrophysiological abnormalities in cardiomyocytes. Mutations in genes encoding ion channel proteins expressed in the myocardium, and their modulators, is the basis of these diseases. This fact is accounted for the unification of these diseases in the group of «channelopathies». The article presents the current diagnostic criteria for these diseases and treatments. In 2011 Guidelines of the European Society of Cardiology for genetic research in channelopathies and cardiomyopathies that have defined the indications for genetic research in this pathology, were issued.